Local corruption and support for fuel subsidy reform: Evidence from Indonesia - Kyle, Jordan (International Food Policy Research Institute, 2017)
There is an urgent need to phase out global petroleum subsidies, due to the severe strain they impose on government expenditures and on the environment. However, reform efforts are often stymied by popular resistance to subsidy reform. This article examines the role played by local governments in shaping resistance to reforming fiscally and environmentally disastrous fuel subsidies. Shifting from universalaccess social programs, such as fuel subsidies, to targeted programs requires vesting authority with local politicians and bureaucrats, whom the state relies on to identify poor households and to deliver benefits. Where local governments are corrupt, citizens find promises to replace fuel subsidies with targeted spending less credible, and resistance to reform is higher. Using household survey data from Indonesia, this paper finds that corruption in the implementation of targeted transfer programs increases resistance to fuel subsidy reform among the poor citizens who consume the least fuel and who stand to benefit the most from targeted programs. Matching methods are employed to reduce endogeneity concerns. The findings suggest that improving capacity within subnational governments to deliver social programs is important in developing public support for reform.